Further evidence for GRIN2B mutation as the cause of severe epileptic encephalopathy. Issue 12 (8th September 2016) - Smigiel, Robert; Kostrzewa, Grazyna; Kosinska, Joanna; Pollak, Agnieszka; Stawinski, Piotr; Szmida, Elzbieta; Bloch, Michal; Szymanska, Krystyna; Karpinski, Pawel; Sasiadek, Maria M.; Ploski, Rafal
Abstract : Epileptic encephalopathies (EE) include a range of severe epilepsies in which intractable seizures or severe sub‐clinical epileptiform activity are accompanied by impairment of motor and cognitive functions. Mutations in several genes including ion channels and other genes whose function is not completely understood have been associated to some EE. In this report, we provide a detailed clinical description of a sporadic male patient with early‐onset epilepsy and epileptic encephalopathy in whom we performed complete exome sequencing (WES) and identified a GRIN2B mutation. The GRIN2B splicing mutation in intron 10 (c.2011‐1G>A) was revealed in a WES study. The result was confirmed by Sanger sequencing. No mutation was found in both parents. Our finding confirms that early‐onset EE may be caused not only by gain‐of‐function variants but also by splice site mutations—in particular those affecting the splice acceptor site of the 10th intron of the GRIN2B gene. © 2016 Wiley Periodicals, Inc.